Peranan Media Animasi Interaktif Untuk Mengenalkan Nilai-Nilai Keagamaan Di Sekolah Dasar - Fadilla, Nur; Yunita Sari, Irma; Arafah, Febriyanti; Nur Azmi, Nabilah (LP2M STAI Darul Kamal NW Kembang Kerang, 2023)
Abstract The era of technology presents a number of problems, especially for educators and students. The younger generation, namely many students who like social media to surf in the midst of their activities, with technological disruption various foreign cultures can easily enter their search. If Western culture is not filtered properly, it will have fatal consequences for the sense of nationalism in the younger generation and even erode the religious values of students. This article aims to describe the application of interactive animation-based learning media to introduce religious values to students, especially at the elementary school level. The method used is a qualitative method with a descriptive analysis approach. The technique of collecting data is based on a study of the relevant literature. The results of the study show that learning using interactive animation media is effective in learning. Many benefits can be obtained from the use of interactive animation media, including: through interactive animation media, the delivery of material is clearer and not only verbal; interactive animation can also overcome limited sensory power and time. Examples such as the animations Nussa Rara and Riko The Series can be used to instill good religious and moral values in elementary school children, including serving both parents, learning to pray, eating manners, dhikr, and monotheism. The implementation of these character values can be taught by educators to students in learning through habituation. Then educators and parents can provide exemplary character values through activities in everyday life.